Doyens of Wielkopolska University Orthodontics, Professors Tadeusz Ziółkiewicz, Barbara Perzyna and Danuta Kazmierczak (Journal of Face Aesthetics, 2024)
The history of the development of medical and dental sciences, is inextricably linked to outstanding, distinguished figures. In orthodontics, which is largely directed at improving facial aesthetics, the main figures were the late Professors, heads of orthodontic university research and teaching units: Tadeusz Ziółkiewicz, Barbara Perzyna and Danuta Kazmierczak. Each of these Professors has made a golden record both in the university community and in the medical community of the Wielkopolska region of our country.
Keywords: doyens; orthodontists; professors at Poznan University of Medical Sciences; Tadeusz Ziółkiewicz; Barbara Perzyna; Danuta Kaźmierczak